CFTR interacts with Hsp90 and regulates the phosphorylation of AKT and ERK1/2 in colorectal cancer cells. Issue 6 (29th April 2019) - Liu, Kaisheng; Jin, Hongtao; Guo, Yaomin; Liu, Ying; Wan, Yong; Zhao, Pan; Zhou, Zhifan; Wang, Jianhong; Wang, Maolin; Zou, Chang; Wu, Weiqing; Cheng, Zhiqiang; et al.
Abstract : Cystic fibrosis (CF) is caused by mutations in the cystic fibrosis transmembrane conductance regulator ( CFTR ) gene. CF cells and tissues exhibit various mitochondrial abnormalities. However, the underlying molecular mechanisms remain elusive. Here, we examined the mechanisms through which CFTR regulates Bcl‐2 family proteins, which in turn regulate permeabilization of the mitochondrial outer membrane. Notably, inhibition of CFTR activated Bax and Bad, but inhibited Bcl‐2. Moreover, degradation of phosphorylated extracellular signal‐regulated kinase 1/2 (ERK1/2) and AKT increased significantly in CFTR‐knockdown cells. Dysfunction of CFTR decreased heat‐shock protein 90 ( Hsp90 ) mRNA levels, and CFTR was found to interact with Hsp90. Inhibition of Hsp90 by SNX‐2112 induced the degradation of phosphorylated AKT and ERK1/2 in Caco2 and HRT18 cells. These findings may help provide insights into the physiological role of CFTR in CF‐related diseases. Abstract : Knockdown of CFTR induces downregulation of Hsp90, and disruption of the CFTR/Hsp90 interaction induces mitochondrial dysfunction via degradation of phospho‐AKT and phospho‐ERK1/2 in Caco2 and HRT18 cells.